Antibiotic prescribing practice in the management of cough or diarrhea among children attending hospitals in Addis Ababa: a cross-sectional study - Tekleab AM; Asfaw YM; Weldetsadik AY; Amaru GM (Dove Medical Press, 2017)
Atnafu Mekonnen Tekleab, Yemisrach Mekonnen Asfaw, Abate Yeshidinber Weldetsadik, Gesit Metaferia Amaru Department of Pediatrics and Child Health, St Paul’s Hospital Millennium Medical College (SPHMMC), Addis Ababa, Ethiopia Background: Irrational use of antibiotics is a global problem. Failure to follow clinical guidelines is one of the main reasons for irrational use of antibiotics. Cough and/or diarrhea are the main childhood illnesses in Ethiopia, and health care providers are expected to follow the national guideline while managing these illnesses. This study tried to assess the extent of adherence to the guideline while managing cases of childhood diarrhea and/or cough.Methods: The study was conducted in 23 hospitals in Addis Ababa. Data were collected prospectively from April to June 2016 using a structured questionnaire. A total of 1,073 children aged 2–59 months who visited the hospitals for cough or diarrhea during the study period were included in the study. Equal number of cases were allocated to each hospital and consecutive cases were included in the study until the calculated sample size was attained for each hospital. Data collectors approached cases after they were seen by the health care provider. SPSS version 20 was used to analyze the data.Result: Of the total number of cases, an antibiotic was prescribed for 794 (74.0%) of the children. Cotrimoxazol 209 (26.3%), amoxicillin 185 (23.3%), and cephalosporines 174 (21.9%) were the three most commonly prescribed antibiotics. Six hundred eighty-eight (86.6%) of the prescriptions were determined to be inappropriate. Of the inappropriate prescriptions, 631 (91.7%) were for prescribing antibiotics when not necessary and 57 (8.3%) were for prescribing the wrong spectrum of antibiotics. Using multivariate analysis, a child not having diarrhea was independently associated with appropriate antibiotic prescription (adjusted odds ratio =0.261, 95% confidence interval: 0.095–0.714). The prescriber being qualified as a pediatrician was an independent predictor of inappropriate antibiotic prescription (adjusted odds ratio =9.967, 95% confidence interval: 4.221–23.532).Conclusion: The magnitude of inappropriate antibiotic prescription while managing cough and/or diarrhea in our setting was high. It needs urgent action to prevent emergence of antibiotic-resistant microorganisms. Keywords: diarrhea, cough, inappropriate antibiotic prescription, hospital, Addis Ababa